Research on Monitoring Technology for Insulation State of Distribution Transformer Winding Based on Finite Element Analysis - Zhang, Jingshuo; Yoon, Minhan (Journal of Ecohumanism, 2024)
This study aims to optimize the insulation state monitoring technology of distribution transformer winding through finite element analysis （FEA） to improve the operation safety and life of power equipment. The paper firstly establishes the coupling simulation model of transformer winding and analyzes the insulation performance under different working conditions. Through simulation data analysis, the key factors affecting insulation aging and the characteristic model of insulation deterioration are constructed. In addition, the research also discusses the application of big data and artificial intelligence in the monitoring technology, which provides a new idea for the intelligent monitoring and optimization of the transformer insulation state. This study not only provides a new technical means for insulation state monitoring, but also provides theoretical support and technical basis for the reliable operation and life extension of power equipment.